Sanksi Pidana Penyebar Berita Bohong (Analisis Putusan Pengadilan Negeri Padangsidimpuan Nomor 148/Pid.Sus/2021/PN Psp). - Walidain, Minsor (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The problem in this study is that the current judge's decision or court decision provides sanctions to perpetrators of crimes or violations according to the author, which does not provide a deterrent effect on perpetrators, so that these sanctions do not create a deterrent effect for perpetrators who commit crimes or violations. Therefore, crimes or violations are currently increasingly prevalent in everyday life. This type of research is a field research (Field Research), which is a research conducted in the real life arena, while the data needed is about theories regarding the law of spreading fake news where the research observes and participates directly in small-scale social research and observes the subject/object of the research. The results of this study are that Yanharis Bangsawan or the Defendant was right to have spread fake news on social media Facebook during the trial, the accusations made by the defendant against the victim were not proven to be true when the trial the judge also examined the chronology. Therefore, judges may not impose sanctions or decide on a case in a trial by themselves, it takes a certain consideration and reasons. The judge gives the sanction of the decision in a trial. However, the reason for the judge Number 148/Pid.Sus/2021/PN Psp, according to the author, is still lacking because the defendant has never been convicted or committed a criminal act, the sanction is reduced even though in this case the defendant had the intention of committing a criminal act.